The Effectivity of Scirpus Grossus and Limnocharis Flava As Fitoremediation Agents of Nitrate-Phosphate To Prevent Microcystis Blooming In Fresh Water Ecosystem - Aliyah Siti Sundari; Catur Retnaningdyah; Soeharjono Soeharjono (Journal of Tropical Life Science, 2013)
The aims of this study were to reduce the concentration of dissolved nitrate-phosphate, furthermore it can inhibit the growth and prevent the occurrence of Microcystis bloom waters. The study was conducted experimentally in the laboratory. The Microcystis isolation carried out in Sutami reservoir. Then, remediation treatment with hydromacrophyte (Scirpus grossus, Limnocharis flava and combination of both hydromicrophyte) were done during 15 day incubation period. Abiotic factors were measured on day 0, 6, 12 and 15, but the abundance of Microcystis cells was counted daily. The productivity of hydromacrophyte was measured at the end of the research. The research results showed that hydromacrophytes were effective to reduce nitrate and phosphate concentrations. Combination of S. grossus and Microcystis reduced nitrate concentration up to 99.89 %, while highest reduction of dissolved phosphate (98.22 %) carried out by combination of L. flava and Microcystis. The combination treatment of L. flava and S. grossus was capable to prevent Microcystis growth rate and carrying capacity that is 65 cells.L-1.day-1 and 6.93 x 104 cells/mL.